Ergonomic position and musculoskeletal disorders in Hasanuddin University Dental Hospital, Indonesia: Posisi ergonomik dan gangguan muskuloskeletal di Rumah Sakit Gigi dan Mulut Universitas Hasanuddin, Indonesia - Fuad Husain Akbar (Makassar Dental Journal, 2021)
Musculoskeletal disorders (MSDs) are the single most common cause of long-term pain and disability affecting hundreds of millions of people, which have been reported to be work-related. Dentist is one of the professions with the highest risk of de-veloping this disease. This study aims to see the level of complaints, assess the musculoskeletal risk and attacks in students at the Hasanuddin University Dental Hospital. A cross-sectional study was conducted on 83 residents and dental interns. A struc-tured questionnaire was employed to gather data, the Nordic Musculoskeletal Questionnaire (NMQ), Rapid Entire Body As-sessment (REBA) and Rapid Upper Limb Assessment (RULA), Quick Exposure Check (QEC). The data were analyzed using SPSS software (version 22) with Chi-Square significance and Pearson correlation test. Strong positive correlation was found between the existing incidence and risk (r=0.832) and there was a very significant relationship between incidence and MSDs (p<0.01). It was concluded that there is a relationship between ergonomic position and musculoskeletal disorders in students at HUDH. The high prevalence of MSDs and the high level of risk, as well as the attack rate based on REBA and QEC indicate im-proper and incorrect ergonomic posture habits.